Does Capital Structure, Audit Quality, and Company Profitability Have an Impact on Accounting Conservatism? - Siregar, Nurhayati; Puspita Sari, Silvia Waning Hiyun; Widayanti, Ipuk; Hasbi, M. Zidny Nafi'; Aziz, Abdul (Universitas Muhammadiyah Semarang, 2023)
This study examines several factors that influence accounting conservatism: Capital Structure, Audit Quality, and Company Profitability. This study uses quantitative methods. All the manufacturing businesses included in this study are listed on the Indonesia Stock Exchange. Purposive sampling is the foundation of the sample selection technique. Panel regression, an analytical technique combining cross-sectional and time-series data, was employed in this study. The results showed that the capital structure variable did not affect accounting conservatism. Then, the audit quality variable significantly affects accounting conservatism, and the company's profitability variable does not affect accounting conservatism